Exploring the link between adenovirus infection and Guillain-Barré syndrome in children: a case-based analysis - Tuychiboeva, Gulrukh; Öncel, İbrahim and Çoban Çifci, Gökçen and Cengiz, Ali Bülent and Aykaç, Kübra (The Turkish Journal of Pediatrics, 2026)
Background. Adenovirus infections are commonly associated with respiratory tract infections, conjunctivitis, gastrointestinal disturbances, and in some cases, more severe illnesses such as pneumonia. Guillain-Barré syndrome (GBS), a rare autoimmune disorder that causes progressive peripheral nerve inflammation and paralysis, has been linked to various infections, including viral ones. Case Presentation. We describe two newly diagnosed pediatric cases of GBS following adenovirus infection. Both patients were previously healthy boys, aged 3 and 6 years. Adenovirus was detected by nasopharyngeal PCR shortly preceding the neurological manifestations. Both were treated with intravenous immunoglobulin (IVIG); one also required plasma exchange and respiratory support. Both recovered fully during follow-up. Additionally, a relevant case from the literature was reviewed for comparison. Treatment included respiratory support, IVIG and plasma exchange therapy. During the 12-month follow-up no severe complications were observed in our patients. Conclusions. In conclusion, while GBS is a well-established complication of several viral infections, including adenovirus, the association between adenovirus and GBS remains relatively underexplored. Our case reports, along with a review of the literature, highlight the rare but plausible link between adenovirus infection and the development of GBS. Although adenovirus infections are common, the occurrence of GBS following these infections appears to be uncommon, suggesting that additional factors may be at play. However, given the potential severity of GBS and the growing body of evidence, it is important for clinicians to remain vigilant for this rare complication in patients with a history of adenovirus infection.